Challenges of Providing Transitional Care and Empowerment for Individuals with Intellectual Disabilities (ID): A Qualitative Study of Families’ Experiences through Guardian Interviews - Alatawi, Marwan (Journal of Ecohumanism, 2024)
This study aimed to explore the challenges and strategies associated with transitional care for individuals with intellectual disabilities (ID) through interviews with 12 guardians. The research identified key issues including system fragmentation, the inadequacy of tailored services, and the critical role of informal support networks. Findings reveal that guardians experience significant difficulties navigating a fragmented care system and face challenges in accessing services that meet their loved ones' specific needs. Despite these obstacles, guardians employ proactive strategies, such as developing personalized care plans and fostering independence and self-advocacy, to manage the transition effectively. The study emphasizes the need for integrated care models and tailored support services, as well as support for guardians in care planning. It also highlights the importance of strengthening informal support networks. Limitations include the small sample size and reliance on self-reported data, which may impact the generalizability of the findings. Future research should explore broader populations and conduct longitudinal studies to assess the long-term effectiveness of transitional care interventions. Overall, this study has provided valuable insights for improving transitional care programs and supports the development of more coordinated, responsive, and personalized care strategies for individuals with ID.